Chitin synthase III: Synthetic lethal mutants and “stress related” chitin synthesis that bypasses the CSD3/CHS6 localization pathway - Osmond, Barbara C. (The National Academy of Sciences, 1999)
We screened Saccharomyces strains for mutants that are synthetically lethal with deletion of the major chitin synthase gene CHS3. In addition to finding, not surprisingly, that mutations in major cell wall-related genes such as FKS1 (glucan synthase) and mutations in any of the Golgi glycosylation complex genes (MNN9 family) are lethal in combination with chs3Δ, we found that a mutation in Srv2p, a bifunctional regulatory gene, is notably lethal in the chs3 deletion. In extending studies of fks1-chitin synthase 3 interactions, we made the surprising discovery that deletion of CSD3/CHS6, a gene normally required for Chs3p delivery and activity in vivo, was not lethal with fks1 and, in fact, that lack of Csd3p/Chs6p did not decrease the high level of stress-related chitin made in the fks1 mutant. This finding suggests that “stress response” chitin synthesis proceeds through an alternate Chs3p targeting pathway.